2016
DOI: 10.1097/md.0000000000005467
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of vitamin K antagonist in atrial fibrillation patients with previous ulcer bleeding

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…In the present study, we found a rate of MACE of 5% per year, which is consistent with other reports 27, 28. This is in accordance with Gallego et al, who found in a cohort of 529 AF patients a rate of thrombotic/cardiovascular events of 5.17% per year in a median follow‐up of 28 months28.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we found a rate of MACE of 5% per year, which is consistent with other reports 27, 28. This is in accordance with Gallego et al, who found in a cohort of 529 AF patients a rate of thrombotic/cardiovascular events of 5.17% per year in a median follow‐up of 28 months28.…”
Section: Discussionsupporting
confidence: 94%
“…In the subgroup of 458 patients treated with warfarin, the rate of MACE was 5.4% per year. 27 Our results are also in keeping with a prespecified analysis from the ROCKET-AF trial, which showed that AF patients with prior cardiac events are at higher risk of MACE than cardiovascularfree patients. 29 The novel finding of the present study is that patients experiencing MACE disclosed significantly higher values of LPS, as compared with patients free from events during follow-up.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, esophagogastroduodenoscopy confirmed ulcer healing before initiation of OAC significantly reduces the rate of major bleeding [ 44 ]. Also, good (>65%) opposed to poor (<65%) TTR did not increase the risk of a recurrent ulcer bleeding but provided better stroke prevention [ 42 ]. The optimal time window of reinitiating OAC following gastrointestinal bleeding remains unclear.…”
Section: Aspects Of Successful Long-term Antithrombotic Managementmentioning
confidence: 99%
“…Among those with gastrointestinal bleeding, gastric and duodenal ulcers are the most common etiologies, accounting for approximately 45–70% of total cases ( 4 , 5 ). A retrospective study in AF patients with a history of ulcer bleeding showed warfarin failed to improve outcomes, as the modest benefit in reducing major adverse cardiovascular events was offset by increased gastrointestinal bleeding ( 6 ).…”
Section: Introductionmentioning
confidence: 99%